Pengaruh Profitabilitas, Capital Intensity, dan Ukuran Perusahaan Pada Tax Aggressive - Kadek Ari Adnyani, Ni; Bagus Putra Astika, Ida (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.08.NO.06.TAHUN 2019, 2019)
Tax aggressiveness in this study is proxied by Net Profit Margin (NPM) Index. The purpose of this study is to obtain empirical evidence regarding the effect of profitability, capital intensity, and firm size on tax aggressive. This research was conducted on property and real estate companies listed on the IDX for the period 2015-2017. Sampling uses non probability sampling techniques with purposive sampling method. 35 companies were selected as samples. The data analysis technique used is multiple linear regression. Based on the results of data analysis, it shows that the variables of profitability, capital intensity, and company size have a positive effect on tax aggressive